Immune dysregulation is an important factor in the underlying complications in Influenza infection. ApoH, IL-8 and IL-15 as markers of prognosis - Garcinuño, Sara; Lalueza, Antonio; Gil-Etayo, Francisco Javier; Díaz-Simón, Raquel; Lizasoain, Ignacio; Moraga, Ana; Diaz-Benito, Blanca; Naranjo, Laura; Cabrera-Marante, Oscar; Pleguezuelo, Daniel Enrique; Ruiz-Ruigomez, Maria; Ayuso, Blanca; et al. (Frontiers in Immunology, 2024)
Influenza virus infection can cause a range of clinical symptoms, including respiratory failure (RF) and even death. The mechanisms responsible for the most severe forms of the disease are not yet well understood. The objective is to assess the initial immune response upon admission and its potential impact on infection progression. We conducted a prospective observational study of patients with influenza virus infection who required admission to a tertiary hospital in the 2017/18 and 2018/19 flu seasons. Immune markers, surrogate markers of neutrophil activation, and blood levels of DNase I and Apolipoprotein-H (ApoH) were determined in the first serum sample available during hospital care. Patients were followed until hospital discharge or death. Initially, 792 patients were included. From this group, 107 patients with poor evolution were selected, and a random control group was matched by day of admission. Patients with poor outcomes had significantly reduced ApoH levels, a soluble protein that regulate both complement and coagulation pathways. In multivariate analysis, low plasma levels of ApoH (OR:5.43; 2.21-13.4), high levels of C-reactive protein (OR:2.73: 1.28-5.4), hyperferritinemia (OR:2.83; 1.28-5.4) and smoking (OR:3.41; 1.04-11.16), were significantly associated with a worse prognosis. RF was independently associated with low levels of ApoH (OR: 5.12; 2.02-1.94), while high levels of IL15 behaved as a protective factor (OR:0.30; 0.12-0.71). Therefore, in hospitalized influenza patients, a dysregulated early immune response is associated with a worse outcome. Adequate plasma levels of ApoH are protective against severe influenza and RF and High levels of IL15 protect against RF.